Pressure effect on magnetic susceptibility of LaCoO3 - Panfilov, A.S.; Grechnev, G.E.; Zhuravleva, I.P.; Lyogenkaya, A.A.; Pashchenko, V.A.; Savenko, B.N.; Novoselov, D.; Prabhakaran, D.; Troyanchuk, I.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The effect of pressure on magnetic properties of LaCoO3 is studied experimentally and theoretically. The pressure dependence of magnetic susceptibility χ of LaCoO3 is obtained by precise measurements of χ as a function of the hydrostatic pressure P up to 2 kbar in the temperature range from 78 K to 300 K. A pronounced magnitude of the pressure effect is found to be negative in sign and strongly temperature dependent. The obtained experimental data are analysed by using a two-level model and DFT+U calculations of the electronic structure of LaCoO3. In particular, the fixed spin moment method was employed to obtain a volume dependence of the total energy difference Δ between the low spin and the intermediate spin states of LaCoO3. Analysis of the obtained experimental χ(P) dependence within the two-level model, as well as our DFT+U calculations, have revealed the anomalous large decrease in the energy difference Δ with increasing of the unit cell volume. This effect, taking into account a thermal expansion, can be responsible for the temperatures dependence of Δ, predicting its vanishing near room temperature.